Everybody votes for Heimat: a study to examine the affective influence of feelings of Heimat on the persuasive impact of political advertising - Mayer, Fabian; Schramm, Holger (Frontiers in Communication, 2024)
Contemporary events are marked by profound social changes and the resulting insecurity among many people. Political appeals on an emotional level and beyond facts are therefore currently popular. The German construct of Heimat conveys feelings of safety and shelter like no other. It is therefore not surprising that the term is instrumentalized in political advertising across the entire party spectrum in Germany. In an empirical study, the influence of Heimat references in visual political advertising on the attitudes of recipients is examined, whereby the feelings of Heimat evoked are modelled as a mediator of this relationship. It is assumed that the strength of this affective influence depends on the moderators information processing (heuristic or substantial) and the personality expression on the factor neuroticism. Party identification complements the model, also moderated by information processing, as an additional factor influencing political attitudes. The results show, however, that the explanatory power for the feeling of Heimat is rather to be found in the identification with the communicating party. Against this background, the persuasive instrumentalization of a feeling of Heimat for the evaluation of political issues can certainly be worthwhile. In this context, it is not decisive whether the content of the advertising material explicitly references the Heimat issue, but how the party itself is perceived by the recipients. No effects were found for personality and information processing.